Corneal Collagen Cross-Linking for Infectious Keratitis: A Systematic Review and Meta-Analysis. Issue 1 (January 2016) - Papaioannou, Lamprini; Miligkos, Michael; Papathanassiou, Miltiadis
Abstract : Purpose: To assess the efficacy of corneal collagen cross-linking (CXL) in the management of infectious keratitis. Methods: Comprehensive literature search was performed in MEDLINE/PubMed and Cochrane Central Register of Controlled Trials using combinations of the following search terms: "corneal collagen cross linking" or "photoactivated riboflavin" or "UVA light and riboflavin" and "infectious keratitis" or "corneal ulcer." Last search was on March 19, 2015. Extracted data from individual studies were summarized and summary proportions of eyes healed and complications for different subgroups were estimated. Results: Twenty-five studies were included (2 randomized controlled trials, 13 case series, and 10 case reports) with a total of 210 eyes of 209 patients, of which 175 eyes underwent CXL. Causative microorganisms were bacteria, fungi, acanthamoeba, and Herpes simplex virus in 96, 32, 11, and 2 cases, respectively. Coinfections were present in 13 and cause was inconclusive in 21 cases. Sixteen of 175 eyes received no additional antibiotics, whereas 159 underwent CXL as an adjunct to antimicrobial treatment. Proportion of eyes healed with CXL was 87.2% (95% confidence interval (CI), 81.9%, 91.8%). For bacterial keratitis, the proportion of eyes healed was 85.7% (95% CI, 78.5%, 91.7%), whereas 10/11 and 25/32 eyes with acanthamoeba and fungal keratitis, respectively, were healed (available data not sufficient to provide a valid proportion analysis). Treatment resulted in corneal melting and tectonic keratoplasty in both Herpes simplex virus cases. Conclusions: CXL seems promising in the management of infectious keratitis, excluding viral infections. However, more randomized controlled trials are required to assess its efficacy. Abstract : Supplemental Digital Content is Available in the Text.